The global burden of bladder, kidney, and prostate cancers attributable to smoking from 1990 to 2021 and projections for the next two decades: A cross-sectional study - Xiangyu Chen+; Xuexue Hao+; Jinhao Wu+; Xiaoqiang Liu (Tobacco Induced Diseases)
Introduction Smoking increases the risk of bladder and kidney cancers and is associated with a poorer prognosis in prostate cancer (PCa) patients, which poses a significant health and socioeconomic burden. Understanding the epidemiologic trends of urological cancers attributable to smoking is critical to developing targeted prevention strategies. This study examines global trends in the three urological cancers attributable to smoking from 1990 to 2021 and projects future trends over the next two decades.